Direct Method in Small Group ELT Sessions: Investigating Students’ Perceptions of Comprehension and Engagement - Adzanil, Fuad Nabil; Mukminatien, Nur; Suryati, Nunung (At-Taqaddum, 2025)
Direct Method is a teaching strategy that emphasizes the full use of the target language. Its application can encourage students' active engagement and in-depth understanding of the target language. However, its application in large groups has several limitations, such as limited time for individual feedback and low student participation. Therefore, the use of the Direct Method in small group sessions can improve students' comprehension and engagement in English learning. This study explored students' perceptions of the Direct Method in ELT small group sessions, focusing on comprehension and engagement. Using a qualitative approach, data were collected through semi-structured interviews with five English Language Education students who had experienced the application of the Direct Method in small group sessions. The results showed that the Direct Method significantly improved students' comprehension, especially in vocabulary, listening, and speaking skills, by familiarizing them with English and providing opportunities for them to express their ideas. Furthermore, the small group sessions allowed for more focused interaction between teachers and students, resulting in more detailed feedback and increased student confidence. The study also highlighted the importance of teachers as a key role in fostering student engagement through interaction, motivation, and feedback, as well as the importance of incorporating relevant and interesting learning topics to increase participation. Despite challenges related to students' varying levels of English proficiency, these findings confirm the effectiveness of the Direct Method in small group sessions in promoting active learning and improving comprehension.